Способы представления польской лингвоспецифической лексики в современном русском интернет-дискурсе - Войцева, Елена Андреевна (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The present paper is devoted to the analysis of ways of expressing Polish specific lexicon in Russian contemporary Internet discourse. The factual material consists of about 500 culture specific words and phrases. Such lexical items serve as means of conveying specific culture-based meanings, characteristic for Polish language.
Keywords: лингвоспецифическая лексика; безэквивалентная; эквивалентная; фоновая лексика интернет-дискурс; польский язык; русский язык; special linguistic lexis; non-equivalent; phon words and word phrases; internetdiscourse; Polish; Russian